Smooth muscle tissue engineering in crosslinked electrospun gelatin scaffolds. Issue 1 (5th October 2015) - Elsayed, Yahya; Lekakou, Constantina; Labeed, Fatima; Tomlins, Paul
Abstract: Crosslinked, multi‐layer electrospun gelatin fiber scaffolds with generally ±45 degree fiber orientation have been used to grow human umbilical vein smooth muscle cells (HUVSMCs) to create a vascular tunica media graft. Scaffolds of different fiber diameter (2–5 μm in wet state), pore size, and porosity (16–21% in wet state) were assessed in terms of cell adherence and viability, cell proliferation, and migration in both in‐plane and transverse directions through the scaffold as a function of time under static cell culture conditions. HUVSMC cell viability reached between 80 and 92% for all scaffolds after 9 days in culture. HUVSMCs adhered, elongated, and orientated in the fiber direction, and migrated through a scaffold thickness of 200–235 μm 9 days post‐seeding under static conditions. The best scaffold was then used to assess the tissue engineering of HUVSMCs under dynamic conditions for a rotating, cell seeded, tubular scaffold in the bioreactor containing the culture medium. Dynamic conditions almost doubled the rate of cell proliferation through the scaffold, forming full tissue throughout a scaffold of 250–300 μm thickness 6 days post‐seeding. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 313–321, 2016.